Hierarchical carbon and nitrogen adsorbed PtNiCo nanocomposites with multiple active sites for oxygen reduction and methanol oxidation reactions. Issue 31 (22nd July 2016) - Wang, Qin; Zhao, Qi; Su, Yiguo; Zhang, Geng; Xu, Guangran; Li, Yingjun; Liu, Baocang; Zheng, Dafang; Zhang, Jun
Abstract : Hierarchical carbon and nitrogen adsorbed PtNiCo nanocomposites with different morphologies and facets were successfully synthesized via a solvothermal method and showed high electrochemical activity and long-term stability towards the methanol oxidation reaction (MOR) and oxygen reduction reaction (ORR). Abstract : Hierarchical carbon and nitrogen adsorbed PtNiCo nanocomposites with different morphologies and facets were successfully synthesized via a solvothermal method and showed high electrochemical activity and long-term stability towards the methanol oxidation reaction (MOR) and oxygen reduction reaction (ORR). Electrochemical results indicated that the (220) facet-terminated PtNiCo@C–N nanocubes manifest superior electro-catalytic activity compared to other morphologies and facets as well as the commercial state-of-the-art Pt/C catalyst (20%). The surface carbon and nitrogen atoms, multiple active surface sites, and synergistic electronic effects of various elements contribute to the high electro-catalytic performance of the electrocatalysts. It is worth mentioning that the carbon and nitrogen atoms were simultaneously adsorbed onto the surface of the catalysts, which can provide more multiple active sites for these nanocomposites. In order to demonstrate this result, a solvent ligand exchange method was explored to demonstrate that these multiple active sites on the surface of the catalysts can be exchanged into n -hexane solution, and thus the catalytic activity dramatically decreased. The present work highlights the carbon and nitrogen adsorbed PtNiCo@C–N nanocomposites as highly active catalysts for polymer electrolyte membrane fuel cells (PEMFCs).